Bottenfärgers läckage av tungmetaller och effekt mot påväxt - En fältstudie om hur olika geografiska områden influerar påväxtgraden och läckaget av tungmetaller - Molén, John; Ingvarson, Hampus (My University, 2015)
For centuries, different techniques has been used to prevent fouling on ships. Today, different types of antifouling paints are used almost exclusively to prevent biofouling to attach to the hull. These antifouling paints contain, and leach substances that can be harmful to the environment, such as copper and zinc. This study aims to describe how fouling varies at different locations in Sweden and the reason for this. Furthermore, the study also outlines how water salinity affects the leakage rate of copper and zinc. In the study, panels painted with five different antifouling paints, was placed at three locations in Sweden. By measuring these panels with an XRF-instrument (X-Ray Fluorescence), before and after the launch, the leakage rate of copper and zinc could be determined. The results from the current study showed the fouling pressure to be higher on the west coast. Some antifouling paints in the study gave a somewhat surprising result, especially in freshwater, where fouling paints with high concentrations of Cu and Zn had a relatively poor effect against fouling. The results also indicate that the leakage rate of Cu increases with increasing salinity. This can also be seen for Zn in antifouling paints for leisure boats, though to a lesser extent. The result for commercial antifouling paints of Zn are the opposite; the leakage rate increases with decreased salinity.
Keywords: Transport; Hållbar utveckling; Transportteknik och logistik; Transport; Sustainable Development; Transport Systems and Logistics